Violence and the State. A Classification Proposal for Just War Theory - Paradela López, Miguel (Foro Interno, 2017)
This article develops a categorization criterion that allows differentiation according to the legitimation of recurring to war as a means of solving conflicts among states, and identifies the main foci of just war theory. In this sense, it distinguishes pacifism, that rejects any kind of violent response by a state; from self-defense, that limits this action to defense against a prior aggression; interventionism, that legitimates military actions in contexts of human rights violations; and warmongering, that denies any kind of limitation in the military reach of states. This article concludes by showing how this proposal provides a parsimonious perspective with the added possibility of summarizing and exhibiting the positions of several scholars on current conflicts.
Keywords: Just war; categorization; violence; state.